Honoring Gülden Özcan: The analytic of loss - Nath, Nisha (Feminist Asylum: A Journal of Critical Interventions, 2023)
Panel Honouring the late Dr. Gülden Özcan, University of Lethbridge, Women Scholars’ Speaker Series